Determination of Oil Palm Leaf Nitrogen Concentration by Reflectance Spectroscopy. - Adni, Ahmad Sarwani (2010)
Nitrogen (N) presents in plant materials usually in the form of protein and its analysis in the laboratory usually involve digestion process. In the digestion process, protein nitrogen is converted to the ammonium form by heating with concentrated sulphuric acid in the presence of a catalyst mixture of sodium sulphate and selenium. The method for determining the final ammonium may be either by distillation, as in the classical Kjeldahl method, or by an instrumental analysis. In recent years, a new method has been developed to measure N content in leaves using a fiber optic spectrometer. This method allows N content in leaves to be determined in situ and it can provide real time data of N content in leaves. Compared to the traditional destructive methods, this method will reduce the cost of analyzing the plant nutrient contents by minimizing chemical cost, time and labor requirements. Furthermore, since this technique does not involve the use of chemicals, there will be no generation of chemical waste. An example of this new method is the miniature fiber optic spectrometer with specially designed leaf probe, the Ocean Optic HR2000 High Resolution Miniature Fiber Optic Spectrometer. However, to get accurate data from this probe, a relationship between the data obtained from the sensor must be correlated with actual foliar nutrient levels measured in the laboratory. Very few studies have been conducted to determine the relationship between the N data obtained using the leaf probe and the N level measured in the laboratory. The objective of this study, therefore, was to determine the relationship between the reflectance measurements using the Ocean Optic HR2000 High Resolution Miniature Fiber Optic Spectrometer with N concentration determined using the traditional wet-chemistry procedure (Kjeldahl digestion technique) from fresh oil palm leaf of different fertilization treatments and from fresh oil palm leaf of different ages. Significant relationships were found between reflectance of fresh oil palm leaves with N from Kjeldahl method. The N concentration in the leaf samples of oil palm from different ages analyzed by the Kjeldahl technique ranged from 1.89 % to 3.24 %. When the oil palm leaves from each field were analyzed separately, the highest relationships were measured in the red region of the spectrum between 699.98 to 700.87 nm. The use of pooled data to obtain the regression equations resulted in precision greater than that achieved with the single-field data. The best regression line in predicting leaf N concentration from the measured reflectance was obtained using the combined (pooled) data and the equation was Leaf N=2.7935-0.0014Reflectance. The difference between the mean of actual N concentration and the mean of predicted N concentration from pooled data was only 0.031%, which was not statistically significant (P ≥ 0.05, df=266) according to the performed t-test. The results indicate that the reflectance spectroscopy method using the Ocean Optic HR2000 High Resolution Miniature Fiber Optic Spectrometer was reliable for the determination of N concentration in fresh oil palm leaves.